1980
DOI: 10.1172/jci109704
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Analysis between the Major Histocompatibility System and Insulin-dependent Diabetes in Families with Patients in Two Consecutive Generations

Abstract: A B S T R A C T INTRODUCTIONOne of the few seemingly well-established facts about the etiology of insulin-dependent diabetes mellitus (IDDM)l is that extensive heterogeneity is present (1-8). Thus, several genetic mechanisms are likely to be involved. These may possibly range from multigenic (with each locus contributing only a small effect) to the major genetic effect of Mendelian modes of inheritance. The recent reports of association between the histocompatibility system (HLA) and IDDM (5,6) indicate a dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 14 publications
5
25
0
Order By: Relevance
“…Since examination of the likeli hoods in the families with only a parent and child affected revealed that they ac count for almost all of the difference in likelihoods between incomplete dominant and incomplete recessive modes of inheri tance. Barbosa et al [1] also found similar results with their two-generation-affected families that the likelihood of the incom plete dominant model is ten times more likely than the incomplete recessive. How ever, one cannot rule out the possibility, as pointed out by Suarez and Van Eerdewegh [25], that this difference may be due to sampling and/or incorrect specification of the true genetic mode of inheritance.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Since examination of the likeli hoods in the families with only a parent and child affected revealed that they ac count for almost all of the difference in likelihoods between incomplete dominant and incomplete recessive modes of inheri tance. Barbosa et al [1] also found similar results with their two-generation-affected families that the likelihood of the incom plete dominant model is ten times more likely than the incomplete recessive. How ever, one cannot rule out the possibility, as pointed out by Suarez and Van Eerdewegh [25], that this difference may be due to sampling and/or incorrect specification of the true genetic mode of inheritance.…”
Section: Discussionsupporting
confidence: 55%
“…It is not possible to compare this find ing with previous studies, since except Barbosa et al [1], who looked at an incom plete dominant mode only when analyz ing their two-generation IDDM families, previous investigators have assumed an incomplete recessive mode of inheritance in their linkage analyses. In our study evi dence for linkage between susceptibility to IDDM and HLA is stronger for a domi nant rather than a recessive model with the same population prevalence.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Similarly, many groups, including our own [10], have shown that the frequency of HLA recombinants in Type I diabetes is normal. Further, it is true that HLA typing does identify siblings of probands at considerably higher risk of diabetes.…”
mentioning
confidence: 55%